A single visit feeding plate for 3 months old cleft palate infant . A case report - Amro Mohammed Moness Ali; Abdullah Kamel (Tabriz University of Medical Sciences, 2017)
Infants with cleft palate (CP) suffer from several difficulties, one of them is feeding, which prevent infant from maintaining adequate nutrition. Usage of feeding plate, special bottles and nipples has been described to overcome this problem. This article describes steps of constructing a single visit feeding plate for a CP infant. The main objective was to provide an infant with a properly functioning feeding prosthesis and to reduce parents' anxiety originated from multiple dental visits. We can conclude that our feeding plate was successfully achieving the planned objectives.